2015
DOI: 10.1186/s12894-015-0062-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and severity of symptoms of pelvic organ prolapse among Emirati women

Abstract: BackgroundSimilar to other Gulf countries, the society in United Arab Emirates is pro-natal with high parity and high prevalence of macrosomic babies. Therefore, it is possible to have a high prevalence of pelvic organ prolapse (POP). Thus, the aim of this study was to determine the prevalence of POP symptoms in one of the UAE cities.MethodsA cross-sectional study of all women who attended the three family development centres was conducted in Al-Ain from January 2010 to January 2011. Non-Emirati, pregnant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 16 publications
3
35
5
1
Order By: Relevance
“…In our study, constipation was an important risk for POP. The results of previous studies are not consistent with this finding 5 , 7 , 23 , 24 . Hendrix et al .…”
Section: Discussioncontrasting
confidence: 64%
“…In our study, constipation was an important risk for POP. The results of previous studies are not consistent with this finding 5 , 7 , 23 , 24 . Hendrix et al .…”
Section: Discussioncontrasting
confidence: 64%
“…Similarly, studies from Nepal42 and Al Ain (UAE)43 indicated that illiterate women were more likely to be affected by POP. Higher risk of POP among illiterate women might be due to higher proportion of delivery at home (83.3%), possibly without the attendance of skilled health professionals.…”
Section: Discussionmentioning
confidence: 95%
“…Owing to different measurement systems and different definition, prevalence of POP among different societies is not consistent. Prevalence of symptom base POP among Emirati women estimated 26.9% by Elbis et al [13]. While Horst et al [14] showed that prevalence of POP with using of pelvic organ prolapse quantification (POP-Q) measurement system is more than 50%.…”
Section: Introductionmentioning
confidence: 99%